Age and reasons for first dental visit: A cross-sectional study of children in Bengaluru, India - Priya Subramaniam; Jyothirmai Reghuvaran (Wolters Kluwer Medknow Publications, 2019)
Background: An early first dental visit lays down the foundation of preventive dental care in order to ensure optimal oral health during childhood. The timing of a child's first dental visit varies in different countries. Aim: The aim of this study was to find the age at which parents first seek dental care for their children in Bengaluru, India, and reasons for the first dental visit. Materials and Methods: A cross-sectional study was conducted across randomly selected dental colleges, private dental clinics, and dental department of hospitals in Bengaluru city, India. Sociodemographic details and reasons for the first dental visit were recorded using a pro forma. Data obtained were subjected to statistical analysis using SPSS software V.22, IBM, Corp., USA. The Chi-square test was used, and the level of significance was set at P < 0.05. Results: The mean age of the first dental visit was 8.18 ± 3.2 years. The maximum number of children reported for their first dental visit at age 6 years. Ninety-six percent of children visited only when there was a problem. Dental pain, dental caries, irregularly placed teeth, deposits, and trauma were found to be significant reasons (P ≤ 0.001). Conclusion: Age 6 years was the most common age for the first dental visit. Pain and dental caries were the most common reasons for the first dental visit.